GARAM BERYODIUM DAPAT MENCERDASKAN ANAK BANGSA DIDUSUN PETE DESA KANIGORO KECAMATAN NGABLAK KABUPATEN MAGELANG - Arif Hartono (Asian Journal of Innovation and Entrepreneurship, 2014)
The state of good nutrition is the main prerequisite in creating a healthy HumanResources and quality. Iodine is one of the nutrients the body needs. Sources of iodineare most commonly found in the community is iodized salt. Iodine deficiency can resultin impaired mental development and brain (or known as Iodine Deficiency Disorders).Still frequently encountered quality and low consumption of iodized salt in thecommunity. this is due to the distribution of iodized salt is not evenly distributed, not allsalts circulating in the community contain enough iodine, iodized salt price differencestend to be more expensive two to three times as well as the lack of public knowledge ofcentrality consume iodized salt. This lack of knowledge led to misconceptions about theneed for quality iodized salt and iodized salt.